2018
DOI: 10.1200/jco.2018.36.4_suppl.214
|View full text |Cite
|
Sign up to set email alerts
|

Molecular and clinical characterization of BRAF mutations in pancreatic ductal adenocarcinomas (PDACs).

Abstract: 214 Background: The activation of the RAS/RAF/MEK/ERK pathway is critical for the proliferation, survival, and tumorigenesis of PDACs. Oncogenic mutations in KRAS (90%) or BRAF (3%) are recurrent genomic alterations, but their co-occurrence is not well described. We reviewed BRAF alterations and clinical outcomes in consecutive PDAC patients (pts). Methods: Perthera, Inc. deploys an IRB-approved registry that was utilized in partnership with PanCAN’s “Know Your Tumor” program. Perthera uses CAP/CLIA accredite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 0 publications
0
19
0
Order By: Relevance
“…A second liver biopsy to better understand the potential mechanism of escape post–dabrafenib treatment was not possible because of the patient's deteriorating clinical condition. Somatic BRAF mutations occur in 3% of pancreatic cancers and are often inversely correlated with KRAS variants (Cancer Genome Atlas Research Network 2017; Guan et al 2018). The ΔNVTAP BRAF has been observed in <0.5% pancreatic cases (Guan et al 2018).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A second liver biopsy to better understand the potential mechanism of escape post–dabrafenib treatment was not possible because of the patient's deteriorating clinical condition. Somatic BRAF mutations occur in 3% of pancreatic cancers and are often inversely correlated with KRAS variants (Cancer Genome Atlas Research Network 2017; Guan et al 2018). The ΔNVTAP BRAF has been observed in <0.5% pancreatic cases (Guan et al 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Somatic BRAF mutations occur in 3% of pancreatic cancers and are often inversely correlated with KRAS variants (Cancer Genome Atlas Research Network 2017; Guan et al 2018). The ΔNVTAP BRAF has been observed in <0.5% pancreatic cases (Guan et al 2018). Here, we show evidence of partial response and direct targetability of dabrafenib in a patient with an identified BRAF in-frame pathogenic deletion that had previously only been described in preclinical studies.…”
Section: Discussionmentioning
confidence: 99%
“…These include the fusion in the neurotrophin receptor tyrosine kinase (NRTK) and ROS1 fusions, NRG1 fusions, ALK rearrangement and BRAF mutations, have been found to be more prevalent than in KRAS mutated PDAC. [86][87][88][89] Fusions in the NRTK gene family leads to a chimeric tropomyosin receptor kinase (TRK) fusion protein and is an oncogenic driver in various types of tumors. Larotrectinib, a TRK inhibitor, has shown efficacy in a phase I-II trial including 1 PDAC, with an ORR of 75%, 90 and is approved by the FDA for any tumor harboring an NTRK gene fusion.…”
Section: Parp Inhibitorsmentioning
confidence: 99%
“…Schreck et al report on two patients with high-grade glioma who were successfully treated with BRAF/MEK inhibition (Schreck et al 2018). In BRAF V600E -mutated pancreatic cancer, within early basket trials, one patient with PDAC responded to vemurafenib (Hyman et al 2015) and another PDAC patient showed prolonged survival under dabrafenib/trametinib combination treatment (Guan et al 2018). In contrast to PDAC, to our knowledge, there have been no reports of BRAF-targeted treatments in PAC patients until today.…”
Section: Discussionmentioning
confidence: 99%